Bränslevalets påverkan på pelletsens förmåga att motstå mekaniskt slitage : En fallstudie vid LKAB i Kiruna - Tegel, Mathias (2013)
This thesis deals with efforts of increasing the quality of a product when the process generating the product was complex. The process studied was complex in that the amount of factors that were believed to affect the different quality aspect was very large, while the many interdependent factors made the relations between the different factors difficult to discover.The process that was investigated was the mining group LKAB's production of iron ore pellet specially developed for direct reduction. The large size of the product makes it demanding regarding the process's ability to satisfy the conditions that the pellets require to obtain a higher resistance to mechanical abrasion. Fine-grained decomposition of the product gives lower revenues and can cause problems in the direct reduction process. It was therefore of interest for LKAB to better understand how the problem could be avoided.Several factors were believed to influence these properties, but the purpose of this study was to specifically explore the impact of the choice of fuel for the burner used in the pelletizing. The burner is used in the pelletizing process to add heat to the process and sinter the pellets, in this case in the production of direct reduction pellets in Kiruna Pelletizing Plant 3. LKAB primarily uses coal as fuel for the burner, but oil is used as fuel in cases when coal for various reasons can’t be used.The relation linked to the choice of fuel and its impact on the pellets resistance to mechanical abrasion were investigated by the use of controlled experiments, and analysis of historical data in the form of an exploratory data analysis and a multiple regression analysis.Based on these analyzes, it was not possible to reveal any clear-cut link between the choice of fuel and the pellets resistance to mechanical abrasion. The analyzes did however mainly point out that if there is a relation, the use of coal is to be preferred as it produces the best pellets in terms of its resistance to abrasion.The recommendations to LKAB that the ...